Difference of Serum MMP9 and TNF ô€ƒ Level in Preterm and Term Premature Rupture of Membranes - Aji P Wibowo; Sri Sulistyowati; Supriyadi H Respati (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To examine the difference between matrix metalloproteinaseâ€ 9 (MMPâ€9) and Tumor Necrosis Factor ô€ƒ (TNFâ€ô€ƒ) serum levels in preterm and term premature rupture of membranes (PROM). Method: Our study employed an observational cross sectional approach. Seventy samples were divided into two groups, 35 samples with preterm PROM (28â€36 weeks gestational age) and 35 samples with PROM at term pregnancy (37â€42 weeks gestational age). Both groups underwent examination for serum MMPâ€9 and TNFâ€ô€ƒ concentration using ELISA method. Statistical analysis was done using ttest. Result: Serum levels of MMPâ€9 in the preterm PROM group was 2860.68K627.32 ng/ml, which was significantly higher than in the PROM at term pregnancy group 2549.74K657.15 ng/ml (p=0.04). Likewise, the average serum level of TNFâ€ô€ƒ in subjects with preterm PROM was 12,086.60K5384.51 ng/ml, significantly higher in comparison to PROM at term pregnancy, which was 6422.51K2645.32 ng/ml (p=0.00). Conclusion: Serum levels of MMPâ€9 and TNFâ€ô€ƒ in preterm PROM is significantly higher than that in PROM at term pregnancy. Keywords: MMPâ€9, premature rupture of membranes, preterm, term, TNFâ€ô€ƒ